The Lipid A from the Haloalkaliphilic Bacterium Salinivibrio sharmensis Strain BAG(T) - Carillo, Sara (MDPI, 2013)
Lipid A is a major constituent of the lipopolysaccharides (or endotoxins), which are complex amphiphilic macromolecules anchored in the outer membrane of Gram-negative bacteria. The glycolipid lipid A is known to possess the minimal chemical structure for LPSs endotoxic activity, able to cause septic shock. Lipid A isolated from extremophiles is interesting, since very few cases of pathogenic bacteria have been found among these microorganisms. In some cases their lipid A has shown to have an antagonist activity, i.e., it is able to interact with the immune system of the host without triggering a proinflammatory response by blocking binding of substances that could elicit such a response. However, the relationship between the structure and the activity of these molecules is far from being completely clear. A deeper knowledge of the lipid A chemical structure can help the understanding of these mechanisms. In this manuscript, we present our work on the complete structural characterization of the lipid A obtained from the lipopolysaccharides (LPS) of the haloalkaliphilic bacterium Salinivibrio sharmensis. Lipid A was obtained from the purified LPS by mild acid hydrolysis. The lipid A, which contains different number of fatty acids residues, and its partially deacylated derivatives were completely characterized by means of electrospray ionization Fourier transform ion cyclotron (ESI FT-ICR) mass spectrometry and chemical analysis.